MANAJEMEN PONDOK PESANTREN DALAM MENINGKATKAN MUTU KUALITAS SANTRI PONDOK PESANTREN DARUSSALAM BLOKAGUNG BANYUWANGI - Rosid, Moh. Harun Al Rosid; Azis, Akyas Abdul (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2022)
Quality management in human resources at Pondok Pesantren Darussalam Blokagung is very important because it will have an impact on the quality of human resources in terms of curriculum, skills, and attitudes which make the education and human resources of Islamic boarding schools Darussalam Blokagung quality so that it is in harmony between general education and madrasah diniyah. also, the need for Islamic boarding schools to support student human resources. The objectives of this study are (1) to describe the quality of students at the Darussalam Islamic boarding school Blokagung, (2) to describe the development of human resources in the Darussalam Islamic boarding school Blokagung, (3) to find out programs to increase the human resources of students at the Darussalam Islamic boarding school Blokagung. This study uses a type of field research using qualitative descriptive research, which is a research procedure that produces descriptive data in the form of written words or speech from people and behavior that can be seen. There are two sources of data in this study, primary and secondary. The data collection techniques are (1) observation (2) interviews and documentation to measure the validity of the data using triangulation of data sources and methods. the data analysis using the Miles and Huberman model analysis, namely the presentation of data reduction data and conclusions. The results of this study indicate that the management and planning of Islamic boarding schools, in improving the quality resources of students at Pesantren Darussalam Blokagung Tegalsari Banyuwangi is carried out based on the application of 4 functions, namely a) planning b) organizing c) implementation (d evaluation.